PENINGKATAN KREATIVITAS DAN HASIL BELAJAR IPA SISWA KELAS 5 SD TARUNA BANGSA MELALUI PENDEKATAN PROBLEM BASED LEARNING - Resty Adelia Novitasari; Indri Anugraheni (Universitas Negeri Medan, 2017)
Abstract : Improving Creativity and Learning Outcomes of Ipa Grade 5 Elementary School Taruna Bangsa Through Problem Based Learning Approach. This study aims to determine the improvement of creativity and learning outcomes of science students 5th grade Taruna Bangsa Elementary School. The research subjects amounted to 31. Power analysis techniques used a comparison analysis of pre-cycle values, cycle I and cycle II. The indicator on the assessment on the improvement of students' creativity in making concept maps is to show the percentage above 70%. In the first cycle there is still one group with a percentage value of 63% and it is below the 70% success rate prsentase. In cycle II the percentage value of all groups increased and none were below the 70% percentage. Indicator of success if 85% of students reach KKM≥70 in science lessons. Before the action the average score reached 69 with a total of 13 complete students (42%) and 18 students unfinished (58%). After being given action in cycle I, the average score reached 80 students with 5 unfinished students (16%) and 16 students complete (84%). In cycle II, the average score of students increased to 87 with the number of 1 student unfinished (3%) and 30 students complete (97%). Keywords : Creativity, Science Learning Outcomes, Problem Based Learning Approach Abstrak : Peningkatan Kreativitas Dan Hasil Belajar Ipa Siswa Kelas 5 SD Taruna Bangsa Melalui Pendekatan Problem Based Learning. Penelitian ini bertujuan untuk mengetahui peningkatan kreativitas dan hasil belajar IPA siswa kelas 5 SD Taruna Bangsa. Subyek penelitian berjumlah 31. Teknik analisis daya menggunakan analisis perbandingan nilai pra siklus, siklus I dan siklus II. Indikator pada penilaian pada peningkatan kreativitas siswa dalam membuat peta konsep adalah menunjukan presentase di atas 70 %. Pada siklus I masih ada satu kelompok dengan nilai presentase 63% dan itu dibawah nilai keberhasilan prsentase sebesar 70 %. Pada siklus II nilai presentase semua kelompok meningkat dan tidak ada yang di bawah nilai presentase 70 %. Indikator keberhasilan apabila 85% dari siswa mencapai KKM≥70 dalam pelajaran IPA. Sebelum tindakan nilai rata-rata mencapai 69 dengan jumlah 13 siswa tuntas (42%) dan 18 siswa tidak tuntas (58%). Setelah diberi tindakan pada siklus I, nilai rata-rata siswa mencapai 80 dengan jumlah 5 siswa tidak tuntas (16%) dan 16 siswa tuntas (84%). Pada siklus II, nilai rata-rata siswa semakin meningkat menjadi 87 dengan jumlah 1 siswa tidak tuntas (3%) dan 30 siswa tuntas (97%). Kata Kunci : Kreativitas, Hasil belajar IPA, Pendekatan Problem Based Learning